ANALISA IMPEDANSI PENGETANAHAN ELEKTRODA BATANG TUNGGAL DALAM BETON RANGKA BAJA TERHADAP INJEKSI ARUS BOLAK BALIK - Achmad Solichan; Rudy Haryanto (MEDIA ELEKTRIKA, 2010)
Low impedance grounding is necessary to anticipate the return flow that can be directly on the ground. Research caruied out by field observations to determine the impedance value which is derived by a single rod electrode: Testing the impedance by the planting depth electrode arrangement and frequency settings. The results obtained were impedance value to a depth of 50 cm for 3.2 to 4.8 Ω, the depth of 100 cm for 3-4 Ω and 150 cm depth of 0.4 to 0.1 Ω.Key words: Impedance grounding, setting depth grounding.